Glial cell-elicited activation of brain microvasculature in response to brucella abortus infection requires asc inflammasome-dependent IL-1b production - Miraglia, Maria Cruz (2016)
Blood-brain barrier activation and/or dysfunction are a common feature of human neurobrucellosis, but the underlying pathogenic mechanisms are largely unknown. In this article, we describe an immune mechanism for inflammatory activation of human brain microvascular endothelial cells (HBMEC) in response to infection with Brucella abortus. Infection of HBMEC with B. abortus induced the secretion of IL-6, IL-8, and MCP-1, and the upregulation of CD54 (ICAM-1), consistent with a state of activation. Culture supernatants (CS) from glial cells (astrocytes and microglia) infected with B. abortus also induced activation of HBMEC, but to a greater extent. Although B. abortus-infected glial cells secreted IL-1b and TNF-α, activation of HBMEC was dependent on IL-1b because CS from B. abortus-infected astrocytes and microglia deficient in caspase-1 and apoptosis-associated speck-like protein containing a CARD failed to induce HBMEC activation. Consistently, treatment of CS with neutralizing anti-IL-1b inhibited HBMEC activation. Both absent in melanoma 2 and Nod-like receptor containing a pyrin domain 3 are partially required for caspase-1 activation and IL-1b secretion, suggesting that multiple apoptosis-associated speck-like protein containing CARD-dependent inflammasomes contribute to IL-1b-induced activation of the brain microvasculature. Inflammasomemediated IL-1b secretion in glial cells depends on TLR2 and MyD88 adapter-like/TIRAP. Finally, neutrophil and monocyte migration across HBMEC monolayers was increased by CS from Brucella-infected glial cells in an IL-1b-dependent fashion, and the infiltration of neutrophils into the brain parenchyma upon intracranial injection of B. abortus was diminished in the absence of Nod-like receptor containing a pyrin domain 3 and absent in melanoma 2. Our results indicate that innate immunity of the CNS set in motion by B. abortus contributes to the activation of the blood-brain barrier in neurobrucellosis and IL-1b mediates this phenomenon.